Looking for me - Hoffman, Beth (Pamela Dorman Books/Viking, 2013)
Opening an antiques shop in Charleston after discovering a talent for restoring furniture, Teddi Overman struggles to come to terms with her shattered family and sense of self after receiving news that her long-missing brother might still be alive.